THE IMPACT OF BOPO, CAR AND LDR ON SUPPLY OF CREDIT IN STATE-OWNED BANKS OF INDONESIA, 2000-2016 - Juliana Fransiska Setiawan Doeve; Malik Cahyadin (MESP–FEB UNS, 2018)
In 2016 the credit supply of State-owned Banks of Indonesia has contributed to total banking credit supply about 39.11%. In addition, in 2000-2016 the credit supply of State-owned Banks of Indonesia tend to increase. This research aims to analyze the impact of operational cost of operating income (BOPO), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) on supply of credit in State-Owned Banks of Indonesia in 2000-2016. It refers to Nuryakin and Warjiyo (2007), Satria and Bagus (2010), Febrianto and Muid (2013), Khasanah and Meiranto (2015), Devi (2016), Amelia (2017), Haryanto and Widyarti (2017), Hyun and Rhee (2011), and Lemmon and Michael (2010). Furthermore, this research employs Fixed Effect Model (FEM). The research results show that BOPO has a negative impact and significant on supply of credit, LDR has a positive impact and significant on supply of credit, while CAR has no impact on supply of credit. The recommendation of this research covers: banks should held down operational cost, banks should manage risks on CAR, and banks should keep a level of LDR.Keywords: Supply of Credit, State-Owned Bank, FEM